THE EFFECTIVENESS OF INNOVATION OF DRYING FLOOR ON THE DELAY OF DRYING POSTPONEMENT AND SEED LAYER THICKNESS TOWARDS VIGOUR AND GROWTH OF RICE SEEDS (Oryza sativa L.) - Ami Suryawati; Lagiman Lagiman; Supono Budi Sutoto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
Drying is one of the important post-harvest activities. Limitations on the location of drying, labor and during the rainy season cause delays in drying. Delays in drying and improper seed layer thickness can reduce the quality of the resulting seed. The purpose of this study is to determine the time delay for drying and the maximum thickness of the seed that did not reduce the viability and growth of rice plants. The study used the innovation drying floor of UPT BBP Barongan, Bantul and Split Plot Design with 2 factors. The first factor as Main Plot was the treatment of drying delay: 2.4 and 6 days. The second factor as a sub plot is the thickness of the seed layer: 3, 5, 7, and 9 cm. The treatment is repeated 3 times. The research data were analyzed with Analysis of variance 5% and further tested with DMRT 5% (Duncan's Multiple Range Test). The results showed that the treatment of delaying drying for up to 6 days and the thickness of the seed drying layer up to 9 cm can be tolerated with innovative drying tools so it does not reduce the seed vigour and growth of rice plants. Keyword: drying delay, seed layer thickness, innovation drying floor, rice vigour and growth